Perceptions of higher education reform in Hong Kong: a glocalisation perspective. Issue 3 (8th August 2016) - Lanford, Michael
Abstract : Purpose: In 2012, the eight UGC-funded higher education institutions in Hong Kong completed a multi-year process in which the majority of academic programs were transformed from three-year to four-year undergraduate curricula to accommodate liberal arts education. This article first discusses why stakeholders in Hong Kong felt that reforms were necessary and summarizes the implementation of these reforms. Afterwards, recent literature that has similarly addressed higher education reforms is reviewed. Finally, the results of a qualitative research study, grounded in glocalisation theory, are presented and contextualized. Design/methodology/approach: This paper first draws upon policy documents, newspaper accounts, and other published primary sources for the review of Hong Kong's educational reforms. Subsequently, an exploratory qualitative research design consisting of semi-structured interviews with 23 administrators and professors in Hong Kong is presented. These individuals are designated as "key informants, " as they gave presentations, made speeches, or were otherwise active in conceptualizing Hong Kong's undergraduate educational reform on macro and micro levels. Findings: Four primary findings concerning educational reform in Hong Kong are highlighted. They include 1) tensions between international benchmarking and internal value systems; 2) confusion over multiple educational paradigms; 3) The limited efficacy of outside speakers and leadership; and 4) controversy over outcome-based assessment. Originality/value: First, recent educational reforms in Hong Kong's higher education sector are summarized. Second, the implications of educational reforms for Hong Kong and glocalisation theory are discussed. Third, conclusions that may resonate with educational reform processes in other international contexts are drawn.